Targeting myeloid cells to improve cancer immune therapy - Chen, Hui; Xu, Zihan; Varner, Judith (Frontiers in Immunology, 2025)
Tumor immunosuppression remains a major barrier to effective cancer immunotherapy and is often driven by the immunoregulatory activities of innate immune cells, such as myeloid cells within the tumor microenvironment (TME). Myeloid populations—including tumor-associated macrophages (TAMs), dendritic cells, granulocytes, monocytes and myeloid-derived suppressor cells (MDSCs)—play pivotal roles in dampening anti-tumor immune responses and promoting tumor progression. Recent advances in our understanding of myeloid cell biology have unveiled new therapeutic opportunities to disrupt these immunosuppressive mechanisms associated with tumor inflammation. This review highlights key signaling pathways and surface molecules involved in myeloid-mediated immune suppression, including CSF1R, PI3Kγ, mTOR, Syk, MerTK/Axl, and immune checkpoints such as Trem2, LILRBs, VISTA, and CD40. We examine preclinical and clinical findings that support targeting these pathways to reprogram the TME and enhance anti-tumor immunity. By integrating insights from mechanistic studies and therapeutic development, this review underscores the potential of myeloid cell-targeting strategies as promising adjuncts to current cancer immunotherapies. Finally, we discuss future directions and challenges in translating these approaches into durable clinical benefit.